The impact of forward head posture on the electromyographic activity of the spinal muscles. Issue 2 (April 2021) - Alowa, Zaenab; Elsayed, Walaa
الملخص: أهداف البحث: فحص نشاط عضلات العمود الفقري لدى السيدات ذوات قوام الرأس المتقدمة إلى الأمام ومقارنته بالسيدات ذوات القوام السليم. طرق البحث: شاركت ٦٠ سيدة في الدراسة من مؤسسة واحدة، تراوحت أعمارهن بين ١٨ و٢٩ عاما. تم قياس الزاوية بين الجمجمة والعمود الفقري من المستوى السهمي لتوزيع المشاركات إلى مجموعتين: مجموعة قوام الرأس المتقدمة إلى الأمام (٣٠ سيدة) الزاوية بين الجمجمة والعمود الفقري (٥٣.١ ± ٢.٣)، ومجموعة قوام الرأس السليم/ المجموعة الضابطة (٣٠ سيدة) الزاوية بين الجمجمة والعمود الفقري (٤٣.٠ ± ٣.٦ ). كما تم استخدام جهاز تخطيط العضلات لقياس نشاط العضلات الكهربي لثماني عضلات شوكية (مستويات الرقبة، وأعلى الظهر، وأسفل الظهر) أثناء الوقوف وأثناء حمل وزن باليدين. النتائج: كانت الزاوية بين الجمجمة والعمود الفقري أقل بكثير في مجموعة الرأس المتقدمة للأمام مقارنة بالمجموعة الضابطة (قوام الرأس السليم). وأظهرت مجموعة قوام الرأس المتقدمة للأمام قيم أعلى لنشاط العضلات العنقية الشوكية مقارنة بالمجموعة الضابطة. كما أظهرت عضلات العمود الفقري العنقية اليمنى واليسرى (٧٣٪ و٨٧٪) على التوالي نشاطا للعضلات أعلى من المجموعة الضابطة أثناء مهمة حمل الوزن. ولم يُستدل على اختلاف كبير بين عضلات أعلى الظهر أو العضلات القطنية بين المجموعات. الاستنتاجات: تشير النتائج إلى زيادة الجهد العضلي على عضلات الرقبة والناتج عن قوام الرأس المتقدمة للأمام لموازنة انخفاض زاوية الرقبة ودعمها. قد يتطلب النشاط المتزايد لعضلات الرقبة في حالات قوام الرأس المتقدمة للأمام مجهودا أكبر من عضلات الرقبة وقد يزيد من خطر إصابات العمود الفقري. وفقا لذلك، يوصَى بشدة بالعلاج المبكر لـقوام الرأس المتقدمة للأمام لتجنب التحميل الزائد على عضلات العمود الفقري. Abstract: Objective: This study aims to examine the electromyographic activity of the regional spinal muscle between patients with forward head posture (FHP) and those with a normal cranio-vertebral (CV) angle. Methods: We recruited 60 adult women aged between 18 and 29 years from a single institution. The CV angle was measured in the sagittal plane, which helped us to assign the participants in the FHP group (n = 30) with a large CV angle (53.1 ± 2.3) and the control group (n = 30) with a normal CV angle (43.0 ± 3.6). The surface electromyography (EMG) was used to measure the magnitude of normalised muscle activity of eight spinal muscles (cervical, lumbar, and thoracic levels) while standing and performing a specific manual handling task. Results: The CV angle was significantly lower in the FHP group than in the control group ( p  = .001). The cervical erector spinae (CES) muscle activity was significantly increased in the FHP group compared to that in the control group. The right and left CES of those in the FHP group exhibited 73% and 87%, respectively, higher normalised muscle activity than those in the control group while performing the manual handling task ( p  = .001). No significant difference was detected for the thoracic or lumbar segment muscles between groups. Conclusion: Our results indicate that greater neck muscle demands result from anterior head translation in FHP. This effect is a counterbalance to the reduced CV angle and to support the neck. The increased activity of the neck muscles in FHP could demand more support from the neck muscles and might increase the risk of spinal injuries. Management of FHP is essential to avoid overloading the spinal muscles.